Pengaruh Transfer Pengetahuan Tacit Dan Trust Terhadap Successor Innovativeness Perusahaan Keluarga Universitas Ciputra - Rohmah, Nur Izzatur; Saputra, Ignatius Teddy (PERFORMA, 2022)
Family business in Indonesia gets good development eventhough in world economy condition that still gets unstable and optimist related to perspective development in coming years. The purpose of this research is to see the effect of tacit knowledge transfer and trust on successor innovativeness of Universitas Ciputra family firm. The method that is used in this research is quantitative with multiple linear regression. The population in this research is ninth batch of Universitas Ciputra family business community member. The sample of this research is determined with sampling purposive technique, uses saturated sampling technique and is obtained respondents of 102 people. Data collection uses questionnaires that are measured by using Likert Scale.. The result of this research indicates that tacit knowledge transfer and trust affect significantly on successor innovativeness. Keywords: tacit knowledge transfer, trust, successor innovativeness.